A Qualitative Study on theConcept of Healthy Lifestyle and Factors Affecting the Dormitory Students’ Lifestyle of Shahid Beheshti University - Karimi, Parvane; Zarani, Fariba; Mazaheri Nejad Fard, Golnaz (International Journal of Applied Behavioral Sciences, 2021)
Introduction: Healthy lifestyle can play a significant role in the health and quality of students’ life. The purpose of this study was to investigate the concept of healthy lifestyle among students living in dormitories and factors affecting their lifestyle.Methods: This qualitative exploratory study was conducted as a semi-structured interview with 18 female students residing in the dormitory of Shahid Beheshti University. These students were selected through purposive sampling. Interviews were analyzed in four contexts: the concept of healthy lifestyles, examining students’ lifestyles, evaluating their lifestyles, and factors affecting their lifestyles. Content analysis was used to analyze the data.Results: The results showed that there are two distinct areas regarding the concept of a healthy lifestyle from the students’ perspective: first, the dimensions that the healthy lifestyle contains and second, the principles on which a healthy lifestyle should be based. There were also five groups of factors affecting students’ lifestyles: avoidance of family (e.g. independence), internal factors (e.g. individual characteristics), university and dormitory conditions (e.g. time), relationships (e.g. Roommate), macro factors (e.g. social, economic).Conclusion: According to the results, it seems that the educational and cultural authorities of the universities need to pay more attention to the lifestyle of the students.